Lingkungan Kerja, Stres Kerja dan Motivasi terhadap Kinerja Marketing Executive Mobil di Malang - Irawati (STIE Malangkucecwara Malang), Rina - (STKIP PGRI TULUNGAGUNG, 2020)
The research objective is to determine the effect simultaneously and partially between the work environment, work stress, and motivation on the performance of car marketing executives in Malang. A sample of 65 marketing executives, with data collection techniques using a questionnaire method. The classic assumption test results show that the data are normally distributed, the regression model does not occur heteroscedasticity, and in the regression model multicollinearity does not occur. Correlation coefficient test results show that the relationship between variable X and variable Y is very strong, and the value of R Square of 0.700. This shows that the magnitude of the influence of the work environment, work stress, and motivation on performance by 70%, while the remaining 30% is influenced by other variables not examined in this study. Based on simultaneous tests, the work environment influences performance. The t value of the calculated work stress variable is -1,606 1.67 and sig value is 0.113, with a significance level of 0.005. So, work stress has no effect on performance. The t value of the motivation variable was 3,217 1.67 and the sig value was 0.002, with a significance level of 0.05. So, motivation influences performance. Partially, there are influential variables, namely the work environment (X1) and motivation (X3), and there are variables that have no effect, namely work stress (X2). The dominant variable influencing performance is the work environment (X1).